2017
DOI: 10.1002/ajmg.b.32534
|View full text |Cite
|
Sign up to set email alerts
|

Familial cases and male cases with MECP2 mutations

Abstract: This is the first report of Chinese familial cases with Rett syndrome (RTT) or X‐linked mental retardation (XLMR). RTT is a neurodevelopmental disorder that almost exclusively affects females. Most RTT cases are sporadic. We have studied eight cases with MECP2 mutations in six Chinese families, including three females and five males with RTT or XLMR. All shared identical MECP2 mutations with their mothers. The three females fulfilled the diagnostic criteria for RTT, while the five males were XLMR. A random X‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Several studies, including ours, have shown that male patients who had variants causing typical RTT in females usually presented with severe neonatal encephalopathy and early death. 15,29 Male patients with somatic mosaic variants may have milder phenotypes in comparison with those of female patients with the same variants and a heterozygous genotype primarily because of differences between their MAFs. However, the correlation between MAFs and the severity of the disease, as well as the minimum threshold of MAFs, requires further investigation in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including ours, have shown that male patients who had variants causing typical RTT in females usually presented with severe neonatal encephalopathy and early death. 15,29 Male patients with somatic mosaic variants may have milder phenotypes in comparison with those of female patients with the same variants and a heterozygous genotype primarily because of differences between their MAFs. However, the correlation between MAFs and the severity of the disease, as well as the minimum threshold of MAFs, requires further investigation in a larger cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, MECP2 mutations have been demonstrated to cause various clinical conditions (HGMD), such as Rett syndrome (678 different mutations), MECP2 duplication syndrome (85), X-linked ID (52), neurodevelopmental delay (35), brain abnormalities (26), atypical Rett syndrome (22), and psychomotor developmental delay (14). It has been observed that a majority of patients with MECP2-caused RTT are sporadic [7,20] because most pathogenic mutations in MECP2 are de novo mutations [21]. In many cases, DNMs are likely derived from the X chromosome in male sperms [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Variant type and location do not adequately explain phenotypic variability, as individuals with the same pathogenic variant have clinical presentations varying from ASD, ID, and RTT ( Figure 1 ), and XCI has been proposed to be an important factor in the onset and severity of RTT [ 78 , 79 ]. Phenotypic variation ranging from classical RTT to normal individuals with protective skewing of the X chromosome have been reported [ 78 ].…”
Section: Mecp2mentioning
confidence: 99%